The impact of the United States Preventive Services Task Force (USPTSTF) recommendations against prostate‐specific antigen (PSA) testing on PSA testing in Australia. (22nd August 2016) - Zargar, Homayoun; van den Bergh, Roderick; Moon, Daniel; Lawrentschuk, Nathan; Costello, Anthony; Murphy, Declan
Abstract : Objective: To assess the impact of the United States Preventive Services Task Force (USPTSTF) recommendations on prostate‐specific antigen (PSA) testing, prostate biopsy, and prostatectomy in Australian men based on the available Medicare data. Patients and Methods: Events were identified using Medicare item numbers for PSA testing (66655, 66659), prostate biopsy (37219), prostatectomy (37210), and prostatectomy with lymph node dissection (37211). The occurrences of each procedure was queried per 100 000 capita for consecutive financial years over the period 2000–2015. For each item number, reports were also generated for all Australian States. For PSA testing the data was stratified into three age groups of 45–54, 55–64, and 65–74 years. For assessing the rate of prostatectomy the capita rate values for two item numbers of prostatectomy (37210) and prostatectomy with lymph node dissection (37211) were combined. Results: Steady declines in per capita incidences of all five item numbers assessed were seen for the three consecutive financial years (2013–2015) since the publication of the USPTSTF recommendation statement. These declines were seen across all Australian States. When examining the rate of PSA testing for the three age brackets 45–54, 55–64, and 65–74 years, similar trends were identified. Conclusions: Since the introduction of the USPTSTF recommendation statement there has been a steady nationwide decline in per capita incidences of PSA testing, prostate biopsy, and prostatectomy based on the Australian Medicare data. Whether these declines are in the right direction toward reduction in over‐diagnosis and overtreatment of clinically insignificant prostate cancer or stage migration toward more locally advanced disease due to lost opportunity in diagnosing and treating early clinically significant prostate cancer will remain to be seen.